Genomics reveal population structure, genetic diversity and evolutionary history of Phyllostachys edulis (moso bamboo) in global natural distribution - Li, Fangdi; Fang, Hongfeng; Zhou, Jie; Hu, Shunkai; Cao, Fuliang; Guo, Qirong (Frontiers in Plant Science, 2025)
IntroductionMoso bamboo (Phyllostachys edulis) is widespread in natural forests over large areas in ChinaMethodsHere we collected 193 individuals of moso bamboo from 37 natural populations in China’s distribution area. Genotyping by sequencing (GBS) was employed to elucidate the genetic diversity, genetic structure, selection pressure, history and adaptive distribution prediction of moso bamboo.ResultsThe results revealed that the moso bamboo in China can be divided into central α, eastern β and southern γ subpopulations, with the α-subpopulation presumed to be the origin center. Notably, the genetic diversity of moso bamboo populations were relatively low, and the heterozygotes were excess. At the subpopulation level, the genetic diversity of α-subpopulation was the highest and that of β-subpopulation was the lowest. Analysis of population selection pressure during the transmission of moso bamboo indicated significant genetic differences among subpopulations. Furthermore, 3681 genes related to adaptability, stress resistance, photosynthesis, and hormone were identified from the selected regions. Four SNP markers developed and validated. Based on the population dynamics history and distribution simulation, we found that the distribution of moso bamboo has been influenced by the climate change in geological history.DiscussionThese findings hold significant implications for enhancing our genetic comprehension of bamboo populations and exploring germplasm resources.